2017
DOI: 10.1080/10641963.2017.1334797
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, treatment, control of hypertension, and associated factors: Results from a Turkish national study

Abstract: This study recognized associated risk factors that may guide policies and interventions to enhance awareness, treatment, and control of HT in Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
4
17
1
1
Order By: Relevance
“…The difference in raised blood pressure in men and women (23.09% vs. 14.86%) in Vietnam found in this study was consistent with the findings from previous Vietnamese studies [5, 7, 8, 21]. This pattern was also comparable to other studies carried out in both developed and developing countries [3, 12, 1418, 22]. In contrast to other studies, a meta-analysis of 45 countries found that there was no significant sex-difference in raised blood pressure prevalence [19].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The difference in raised blood pressure in men and women (23.09% vs. 14.86%) in Vietnam found in this study was consistent with the findings from previous Vietnamese studies [5, 7, 8, 21]. This pattern was also comparable to other studies carried out in both developed and developing countries [3, 12, 1418, 22]. In contrast to other studies, a meta-analysis of 45 countries found that there was no significant sex-difference in raised blood pressure prevalence [19].…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of raised blood pressure in the present study is lower than the prevalence of raised blood pressure in selected countries and regions such as Africa (30.8% in 2010) [11], China (from 20.5% to 28.7%) [1216], Labanon (29.3%) [17], and Turkey (24.8%) [18]. Compared with the results from the systematic review and meta-analysis in 2015 comprising data on 45 low- and middle-income countries, which reported the pooled raised blood pressure prevalence of 37.8% (95% CI: 35.0–40.6) in upper middle-income countries and 23.1% (95% CI: 20.1–26.2) in low-income countries, the prevalence in Vietnam is also much lower [19].…”
Section: Discussioncontrasting
confidence: 53%
“…We foundoverweight and obese patients had higherhypertension prevalenceand hypertension and T2DM treatment, but a lowerhypertension control rate. This was in agreement with other studies [25,42].Overweight and obesity increase hypertension and T2DM risks. There is research reporting that obese patients have received medications to lower their lipid, BPs, and plasma glucose levels, but this was correlatedinversely to how well their BP was controlled [43,44].…”
Section: Discussionsupporting
confidence: 94%
“…The prevalence and awareness of hypertension in Iran (compared based on the cut-off of 140/90 mmHg) resemble findings reported in other middle-income countries [26,27]. Despite a higher treatment rate in Iran, the control rate stood at 39.1%, which is yet noticeably lower than Turkey, with 53.9% in 2012, and Lebanon, with 54% in 2014 [28].…”
Section: Discussionsupporting
confidence: 68%